Cultural Influences on Traditional Mosque Architecture: Case Studies of the Katangka and Wapauwe Mosques - Hidayati, Nurul; Can Karagülle (Green Publisher, 2025)
This study examines the influence of local culture on traditional mosque architecture through case studies of the Katangka Mosque in South Sulawesi and the Wapauwe Old Mosque in Maluku. These two mosques represent a form of acculturation between Islamic values and local cultural traditions within their respective regions. The research employs a historical approach and typological analysis to identify architectural elements that reflect the social, cultural, and environmental characteristics of their local contexts. The main focus is directed toward roof forms, spatial layout, material usage, and decorative elements, as well as how these aspects demonstrate adaptation to the local climate and geographical conditions. The findings reveal that both mosques function not only as places of worship but also as expressions of the community’s cultural identity. This study contributes to a deeper understanding of the diversity of religious architecture in Indonesia and offers insights for the contextual and sustainable design of future mosques.